2009
DOI: 10.1016/j.intacc.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family-firm structure and board composition on corporate transparency: Evidence based on segment disclosures in Malaysia

Abstract: The aim of this study is to contribute to the growing literature on the quality of accounting disclosures by family firms by investigating whether the alignment (entrenchment) effect leads to high (low) corporate transparency. Unlike previous studies, this study also examines the relationship between board composition and corporate transparency by distinguishing between the two types of nonexecutive directors, namely independent and affiliated directors. Using the enhanced segment disclosures by Malaysian firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 70 publications
(94 reference statements)
10
66
0
4
Order By: Relevance
“…Studies conducted in emerging markets like Malaysia have reported the ineffectiveness of board characteristics such as board independence in overall improvement on corporate governance to ensure that minority shareholders' rights are protected. Important studies conducted in this regard include Wan-Hussin (2009).Because of the reasons discussed this study has included board size and board independence to study in what manner board is effective with regard to corporate decision making of corporate cash holdings.…”
Section: Board Characteristicsmentioning
confidence: 99%
“…Studies conducted in emerging markets like Malaysia have reported the ineffectiveness of board characteristics such as board independence in overall improvement on corporate governance to ensure that minority shareholders' rights are protected. Important studies conducted in this regard include Wan-Hussin (2009).Because of the reasons discussed this study has included board size and board independence to study in what manner board is effective with regard to corporate decision making of corporate cash holdings.…”
Section: Board Characteristicsmentioning
confidence: 99%
“…Bununla birlikte, büyük işletmeler bölümsel raporlamayı gerçekleştirebilecek sayıda deneyimli personele ve maliyetleri kaldırabilecek düzeyde kaynağa sahiptirler (Mardini vd., 2013: 258). Bu doğrultuda, literatürde yer alan birçok çalışma işletme hacmi ile UFRS 8 uygulamaları arasında pozitif bir ilişki tespit etmiştir (Bradbury, 1992;Herrmann ve Thomas, 1996;Nichols and Street, 2007;Wan-Hussin, 2009;Sucuahi, 2013;Gisbert vd., 2014;Zeytinoğlu 2015;Alanezi vd., 2016). Önceki çalışmalar göz önünde bulundurularak aşağıdaki hipotez geliştirilmiştir.…”
Section: İşletme Hacmiunclassified
“…Bu sonuçlara göre büyük ölçekli işletmeler hem ürün ve hizmetleri ile ilgili hem de coğrafi bölümleri ile ilgili küçük işletmelere göre daha fazla bilgi paylaşımında bulunmaktadırlar. Elde edilen bulgular literatürde yer alan birçok çalışma ile uyumludur (Bradbury, 1992;Herrmann ve Thomas, 1996;Nichols and Street, 2007;Wan-Hussin, 2009;Sucuahi, 2013;Gisbert vd., 2014;Zeytinoğlu 2015). Bölümsel bilgi düzeyi ile işletme büyüklüğü arasındaki pozitif ilişki birçok sebep ile açıklanabilir.…”
Section: İşletmelerin Bölümsel Raporlama Düzeylerini Etkileyen Faktörlerunclassified
“…However, the evidence from Malaysia indicates thatthe independence of the board does not enhance reporting lucidity [Haniffa and Cooke 2002;Wan-Hussin 2009] and restrain corporate restatements [Abdullah, Siddique, and Rahaman 2010], which lends credibility to the view that the presence of independent non-executive directors are merely a box-ticking exercise, is ceremonial and is a form of window dressing.…”
Section: Literature Reviewmentioning
confidence: 99%